Taxes influence on bank leverage and profit shifting - Joia, Arthur José Cunha Bandeira de Mello (2019)
How taxes affect corporate financing decisions is an important question in the capital structure literature and a challenging one to address with empirical data due to several endogeneity issues. Although many studies address this question, there is still no decisive evidence on whether tax effects are relevant, as suggested by the trade-off theory, or of third-order importance, as suggested by other theories, such as the pecking-order and market timing. This situation is especially true for the banking industry, considering that few studies include financial institutions. Regulatory concerns have commonly been accepted as dominant in banks\' capital structure decisions; however, recent studies show that this assumption might be incorrect. Harmful tax competition is a related subject that has received little attention from previous capital structure studies. Profit shifting strategies, such as shifting economic activities, may also be understood as non-debt tax shields. Considering that taxation occurs at the individual firm level and that bank conglomerates have profit shifting opportunities among affiliated firms, I evaluate weather Brazilian banks are able to take advantage of the debt tax shield while accomplishing other capital structure goals at the conglomerate level. As far as I am concerned, this research is the first to gather empirical evidence on this phenomenon. Recent empirical studies have presented convincing results on tax policy changes as natural experiments to try to resolve the endogeneity problem. In this context, a two-step 11 p.p. tax rate increase applied to Brazilian banks\' corporate tax rate, alongside some features of Brazil\'s complex and unstable tax environment, provide a unique study opportunity. This dissertation consists of a quantitative empirical research strategy using a difference-in-differences methodological approach. Results from the first corporate income tax rate increase are consistent with trade-off theory predictions and with the hypothesis that, compared to individual banks, financial conglomerates\' capital structure are less affected by taxes. However, findings from the second event do not support the trade-off predictions. One possible explanation consistent with regulatory dominance on bank\'s capital structure decisions is that Basel III implementation with stricter regulatory requirements left little room for tax effects. Even though results are mixed, this research provides evidence on how tax legislation can be used to help achieve regulatory goals.